Comparison of Contrast Induced Nephropathy in Diabetics and Non-Diabetics after Percutaneous Coronary Intervention in Previously Normal Renal Functions - Zahid Hussain, Iftikhar Ahmed, Faiza Alam, Naveed Ahmed, Attiya Mustafa, Abdul Manaf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the incidence and severity of contrast-induced nephropathy (CIN) in patients who underwent percutaneous coronary intervention at tertiary care hospital of Pakistan. Study design: Prospective analytic cross-sectional study. Place and duration of study: Department of Cardiology of a Tertiary Cardiac Care Center of Pakistan from 1st April 2022 to 30th September 2022. Methodology: Two hundred and fifty patients of coronary artery disease older than 18 years irrespective of gender were enrolled using non-probability consecutive sampling technique. The patients were divided into two groups; diabetic and non-diabetic, who received a contrast medium during the procedure. Results: Thirty seven (14.66%) patients were diagnosed with CIN after percutaneous coronary intervention. Patients with diabetes 25(69%) were more prone to develop CIN compared with non-diabetic patients 12(31%). Also, patients with diabetes have significantly high levels of post procedure creatinine levels compared with the non-diabetic patients. Practical Implication: it is cleared from the body by glomerular filtration. The mechanism of CIN is dependent on the medullary ischemia, oxidative stress and tubular cell toxicity. Conclusion: Contrast-induced nephropathy is a common complication following percutaneous coronary intervention and is more prevalent in diabetic patients. However, none of the patients require hemodialysis. Keywords: Contrast-induced nephropathy, Diabetic, Non-diabetic, Percutaneous coronary intervention, Renal function